(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Folk tales are a major component of folk literature. Folk tales reflect the customs, ideas and imaginations of a nation. In other words, the overall nature of the national life of a nation can be contained in fairy tales. Therefore, the fairy tales prevalent in the Assamese society are naturally involved in various aspects of the Assamese society. Folk tales are an important part of Assamese folk literature and children’s literature. The paper attempts to examine some aspects of the female character reflected in fairy tales based on the folk tales of Laxminath Bezbaruah. Many folk tales in Bezbaruah that feature female characters as the main characters. It is worth noting that most of the folk tales in Bezbaruah’s ’Burhi Asir Sadhu’ are female characters. These include ’Tejimla’,Silonir Jiyekor Sadhu ( ’The Tale of the Daughter of Black Kite’), ’Tula aru Teja’, ’Champavati’, and ’Paneshai’.These folk tales mention women’s activities such as singing, cooking, weaving etc . Other folk tales also mention female characters and various activities of women. In addition to the qualities of women such as honesty, tolerance, sacrifice, etc., the fairy tales also reflect the aspects of women such as jealousy and suspicion. It attempts to analyze the various characteristics of women, the overall status of women characters, the acceptability of character aspects, etc. based on the folk tales of Laxminath Bezbaruah.